2022
DOI: 10.1007/s40261-022-01190-2
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of Non-vitamin K Antagonist Oral Anticoagulants Dosing According to Different Prescription Guides Used in Belgian Ambulatory Care

Abstract: Background Non-vitamin K antagonist oral anticoagulants (NOACs) are the preferred choice of anticoagulants to prevent stroke in most patients with atrial fibrillation (AF). NOAC's dosing algorithms are defined in the respective Summary of Product Characteristics (SmPC) but the European Heart Rhythm Association (EHRA) Practical Guide can also be used as it considers more complex clinical scenarios. Nevertheless, suboptimal dosing of NOACs compromises the efficacy and safety of this commonly prescri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In this cross-sectional retrospective study, clinical pharmacists evaluated 536 AF inpatient records examining anticoagulation regimens based on the latest guidelines and medication labels. Similar studies also evaluated the appropriateness of OAC treatment in patients with AF ( Qian et al, 2021 ; Delesie et al, 2022 ; Moudallel et al, 2022 ) and explored the possible influencing factors regarding inappropriate anticoagulation therapy. Distinct from those studies, our study designed, produced, and disseminated a questionnaire and asked the “no-use of OACs” to verify the influencing factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this cross-sectional retrospective study, clinical pharmacists evaluated 536 AF inpatient records examining anticoagulation regimens based on the latest guidelines and medication labels. Similar studies also evaluated the appropriateness of OAC treatment in patients with AF ( Qian et al, 2021 ; Delesie et al, 2022 ; Moudallel et al, 2022 ) and explored the possible influencing factors regarding inappropriate anticoagulation therapy. Distinct from those studies, our study designed, produced, and disseminated a questionnaire and asked the “no-use of OACs” to verify the influencing factors.…”
Section: Discussionmentioning
confidence: 99%
“…In this cross-sectional retrospective study, clinical pharmacists evaluated 536 AF inpatient records examining anticoagulation regimens based on the latest guidelines and medication labels. Similar studies also evaluated the appropriateness of OAC treatment in patients with AF (Qian et al, 2021;Delesie et al, 2022;Moudallel et al, 2022) The study showed approximately 47.4% (254/536) of the anticoagulation regimens for AF patients upon discharge were inappropriate. The inappropriate sample consisted of 134 (25%) "no-use of OACs", 112 (20.9%) "underdosing-use of OACs", and eight (1.5%) "over-use of OACs".…”
Section: Discussionmentioning
confidence: 99%
“…Having to consider all these three aspects when prescribing, antithrombotic therapy can easily lead to suboptimal therapy and thus increase the risk of a thrombotic event or bleeding. Suboptimal antithrombotic therapy has been studied mostly in secondary care and focused on inappropriate prescribing 10–17. Inappropriate prescribing, for example, underdosing, occurred frequently, which showed antithrombotic therapy being complex.…”
Section: Introductionmentioning
confidence: 99%
“…Suboptimal antithrombotic therapy has been studied mostly in secondary care and focused on inappropriate prescribing. [10][11][12][13][14][15][16][17] Inappropriate prescribing, for example, underdosing, occurred frequently, which showed antithrombotic therapy being complex. Because of this complexity, the pharmacist's expertise should be used.…”
Section: Introductionmentioning
confidence: 99%